IL-33/ST2 Axis Protects Against Traumatic Brain Injury Through Enhancing the Function of Regulatory T Cells - Xie, Di; Miao, Wanying; Xu, Fei; Yuan, Chunling; Li, Sicheng; Wang, Chujun; Junagade, Aditi; Hu, Xiaoming (Frontiers in Immunology, 2022)
Traumatic brain injury (TBI) is a devastating condition due to its long-term sequelae on neurological functions. Inflammatory responses after TBI are critical for injury expansion and repair. Recent research in central nervous system (CNS) disorders reveals the importance of IL-33 and its receptor (ST2) as an alarmin system to initiate immune responses. This study explored the role of IL-33/ST2 signaling in TBI. TBI was induced in adult male C57BL/6J mice using a controlled cortical impact (CCI) model. We found that the expression of IL-33 increased in the injured brain and blood, and ST2 was elevated in the circulating and infiltrating regulatory T cells (Tregs) early after TBI. ST2 deficient mice exhibited reduced Treg numbers in the blood and brain 5 days after TBI. The brain lesion size was enlarged in ST2 knockout mice, which was accompanied by deteriorated sensorimotor function 5 days after TBI. In contrast, post-TBI treatment with IL-33 (2 μg/30 g body weight, intranasal) for 3 days significantly reduced brain lesion size and improved neurological functions 5 days after TBI. Meanwhile, IL-33 treatment increased ST2 expression in circulating and brain infiltrating Tregs. To further explore the involvement of Tregs in IL-33/ST2-mediated neuroprotection, Tregs were depleted by CD25 antibody injection. The absence of Tregs significantly reduced the protective effect of IL-33 after TBI. In vitro study confirmed that IL-33 (50 ng/ml) increased the production of IL-10 and TGFβ from activated Tregs and boosted the inhibitory effect of Tregs on T effector cell proliferation. Taken together, this study suggests that the activation of IL-33/ST2 signaling reduces brain lesion size and alleviates functional deficits after TBI at least partially through regulating the Treg response. IL-33 may represent a new immune therapeutic strategy to improve TBI outcomes.